2015
DOI: 10.1155/2015/216932
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Three Multipurpose Disinfecting Solutions with a Silicone Hydrogel Contact Lens

Abstract: Purpose. To evaluate the clinical performance of a silicone hydrogel (Si-Hy) soft contact lens (CL) in combination with three different multipurpose disinfecting solutions (MPDSs). Methods. This was a prospective, randomized, single-masked, crossover, and comparative study in which 31 habitual soft CL wearers were randomly assigned to one of the three MPDSs (Synergi, COMPLETE RevitaLens, and OPTI-FREE PureMoist) for 1 month with a 1-week wash-out period between each exposure. All subjects were successfully ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…The increase in bulbar redness and limbal redness at the end of the day in the Si-Hy group seems to be related to the presence of the CL on the eye during several hours, despite the high oxygen permeability of the CL used. In a previous study, it was seen that the increases in bulbar redness and limbal redness with the three MPDSs used in this study were similar, supporting the idea that the ocular redness is related with the presence of the CL itself [ 42 ]. Moreover, this result agrees with other authors who observed that the evening peaks of redness coincide with the peak of CL awareness and dryness symptoms [ 2 4 ].…”
Section: Discussionsupporting
confidence: 84%
“…The increase in bulbar redness and limbal redness at the end of the day in the Si-Hy group seems to be related to the presence of the CL on the eye during several hours, despite the high oxygen permeability of the CL used. In a previous study, it was seen that the increases in bulbar redness and limbal redness with the three MPDSs used in this study were similar, supporting the idea that the ocular redness is related with the presence of the CL itself [ 42 ]. Moreover, this result agrees with other authors who observed that the evening peaks of redness coincide with the peak of CL awareness and dryness symptoms [ 2 4 ].…”
Section: Discussionsupporting
confidence: 84%
“…The disinfection efficacy of CLEAR CARE, RevitaLens OcuTec, OPTI‐FREE PureMoist and Biotrue solutions was compared. It resulted that CLEAR CARE cleaned lens cases exhibited much higher bacterial concentration than the ones cleaned with RevitaLens OcuTec . The same result was observed comparing PureMoist with Biotrue.…”
Section: Contamination In Contact Lensessupporting
confidence: 71%
“…Similarly, there have been very few (one) marketed, now discontinued MPS product with any chlorine-based disinfection componentry, and its effectiveness against Acanthamoeba sp. was not reported [ 30 ]. Although our study used a genotypic strain of A .…”
Section: Discussionmentioning
confidence: 99%